PERBANDINGAN KARAKTERISTIK DAUN SINGKONG DI DAERAH RAWAN KEMACETAN DENGAN DAERAH TIDAK RAWAN KEMACETAN - Widiantara, I Kadek; Sri Anjani, Ida Ayu Anggara; Dale, Emanuel; Quivera Nanggor, Arnoldus Patrik (Jurnal Ecocentrism, 2025)
The increasing number of motor vehicles each year has led to worsening air quality, with vehicle emissions being a major source of urban air pollution. This study aims to examine and compare the characteristics of cassava leaves growing in areas prone to traffic congestion. High pollution levels contribute to noticeable changes on the leaf surfaces. The research was conducted by collecting two leaf samples from different locations: (1) a roadside with heavy vehicle traffic and (2) a privately owned garden. The observed parameters included leaf color, texture, and the underside of the leaves. The results showed that cassava leaves exposed to high pollution levels experienced color changes (yellowish spots on the surface), rougher textures, and the presence of black dots or dirt particles on the underside, resembling vehicle emission residues. In contrast, leaves collected from the garden appeared unaffected by such conditions. These findings confirm that vehicle emissions significantly impact the characteristics of plant leaves.